Who dwells in the cities? Exclusions, intersections and crossings - Bonavitta, Paola (Universidad de Lima. Carrera de Arquitectura, 2019)
Postmodern cities represent the logic of ephemeralness and daily consumption. Sometimes streets are ruled by a hectic and fleeting traffic flow. At other times the wounds of resistance do not heal, and they submit to the logic of those who resist and fight. They are cities taken by different bodies: natives, almost local, migrants; each one dwelling in his/her places and no-places. Which bodies can move around postmodern cities? What happens to those who do not have a place in said territories? The urban logic responds to massive consumption. So do its streets. The wound of coloniality does not heal and the spaces, bodies and ownerships are remapped in imaginary cartographies available for the implicit reading of local/regional/global design.